2017
DOI: 10.4103/iju.iju_371_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sterile water irrigation versus intravesical mitomycin C in preventing recurrence of nonmuscle invasive bladder cancer after transurethral resection

Abstract: Introduction:Early recurrence of nonmuscle invasive bladder cancer (NMIBC) following transurethral resection (TUR) remains relatively high. An immediate single instillation of mitomycin C (MMC) reduces the recurrence rates in the first 2 years but has not shown benefits in tumor progression or overall survival. Distilled water irrigation has shown to delay tumor recurrence by osmolysis of tumor cells. There are only limited clinical studies comparing the efficacy of MMC with continuous sterile water irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
1
21
2
Order By: Relevance
“…Our findings have some clinical implications. First, although several studies reported no significant difference in time to IVR between patients treated with CSBI alone and those treated with SIC ( 9 , 10 , 18 ), our results suggest that CSBI can weaken the inhibitory effect of SIC on IVR if it is performed after SIC. Second, irrigation with saline and DXR, which included a low concentration of DXR, did not exert an anticancer effect, meaning that CSBI alone could not have a preventive effect on IVR.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Our findings have some clinical implications. First, although several studies reported no significant difference in time to IVR between patients treated with CSBI alone and those treated with SIC ( 9 , 10 , 18 ), our results suggest that CSBI can weaken the inhibitory effect of SIC on IVR if it is performed after SIC. Second, irrigation with saline and DXR, which included a low concentration of DXR, did not exert an anticancer effect, meaning that CSBI alone could not have a preventive effect on IVR.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, earlier reports suggested that CSBI had a greater preventive effect on IVR compared to SIC ( 9 , 10 , 18 , 19 ). One report showed that there were no significant differences in the median time to first recurrence between patients treated with CSBI and those who underwent immediate SIC with mitomycin C ( 9 ).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In a prospective, randomized, open-label, singlecentre, two-arm pilot study between an immediate MMC instillation after TURBT and sterile water irrigation (CSWI) was undertaken between December 2013 and September 2015 with 19 patients in CSWI group and 15 patients in MMC group. 19 After 12 months, recurrence-free rates were 52% for CSWI group and 47.1% in MMC group. The mean recurrencefree period for CSWI group was 9.8 months and for MMC group 10.9 months.…”
Section: Resultsmentioning
confidence: 89%
“…In a randomized controlled trial, Bijalwan et al . [ 7 ] compared continuous irrigation with sterile water to a single intravesical mitomycin C instillation and detected no significant difference.…”
Section: Can Sterile Water Irrigation Be a Substitute For Single-dosementioning
confidence: 99%